Comparison Between Cracked and Normal Residential House at Peat Soil Area by Using Finite Element Modelling - Mohd Hussin, Mohd Amirul Haqimi; Tuan Chik, Tuan Norhayati (Recent Trends in Civil Engineering and Built Environment, 2024)
Peat soils have a very high moisture content, low bearing capacity, and high compression. Due to its characteristics, peat soil is less preferred for the construction of civil buildings. However, every problem must have a solution, for example needing improvements on peat soil or mitigation technique on building to control the damage on buildings. If the issue persists, contamination from peat must be taken into consideration. It can be unsafe and fail to control. The structural condition of the peat soil will affect humans and severe damage to the building, such as cracks in plaster, cracks in beams, columns, and floors. In addition, it can also cause a building to collapse. Therefore, mitigation techniques are essential to control or reduce the impact of damage to a building erected on the surface of peat soil. Thus, the purpose of this study is to perform a dynamic response on crack and normal residential houses at peat soil area and to compare the performance of both houses by using Finite Element Modelling (FEM). The study will focus on two locations where existing residential buildings are damaged and residential buildings used mitigation techniques. The location of these two buildings is in Ayer Hitam, Muar, Johor. Both of these buildings were modelled with Finite Element Methods (FEM). The Finite Element Analysis, also known as Modal Analysis, was carried out using the ANSYS software. After evaluation, the natural frequency mode shape from building 1 was 3.12Hz, while the natural frequency mode shape from building 2 was 5.98Hz. According to the natural frequency data, Building 1 has the lowest value compared to Building 2. The possibility of lower natural frequency causes building 1 to suffer severe damage, including cracks on non-structural and structural cracks. While building 2 has been strengthened structurally in theory, mitigation has been added to the building to enhance the structure further. However, the value of the natural frequencies of building 2 is more acceptable than the value of the natural frequencies of building 1.